Morphological Diversity of Piperaceae in Bandealit Resort Meru Betiri National Park (TNMB), Indonesia - Selvi D Agustina; Sulifah A Hariani; Kuswati Kuswati; Yayuk Fatmawati (Jurnal Riset Biologi dan Aplikasinya, 2025)
The Piperaceae family is notable for its many benefits to humans due to the production of unique essential oils. The economic, health, and cultural value of this family necessitates the exploration of its diverse species as material alternatives. This study aimed to investigate the Piperaceae family's morphological diversity in the TNMB region. This qualitative research employed a tracking method, and the results indicated the Piperaceae morphological variations through the instruments of root, stem, leave, and flower. The study identified 11 species, including 10 of the Piper genus and one of the Peperomia genus, respectively. The two genera exhibited variations in root and stem morphology. They were similar in leaf shape, aroma, and flower type. Morphological investigation is important for identifying Piperaceae family members, of which few of the 11 identified species have been used. This study provides baseline data that may contribute to future conservation, domestication, and commercialization efforts.